Modelling the thermal evolution of extensional basins through lithosphere stretching factors: application to the NW part of the Pannonian Basin - E. Békési; J.-D. van Wees; J.-D. van Wees; K. Porkoláb; M. Hencz; M. Berkesi (Solid Earth)
The reconstruction of thermal evolution in sedimentary basins is a key input for constraining geodynamic processes and geo-energy resource potential. We present a methodology to reproduce the most important transient thermal footprints accompanying basin formation: lithosphere extension and sedimentation. The forward model solving the transient heat equation is extended with an inversion workflow to constrain models with temperature measurement, providing estimates on model parameters, most importantly the amount of lithosphere stretching. We apply the methodology to the NW part of Hungary. We test the effect of variations in model input parameters on the resulting temperature estimates and discuss the uncertainties and limitations of the modelling technique. Realistic past and present-day temperature predictions for the entire lithosphere are achieved for a carefully assessed set of input parameters, suggesting the strong attenuation of the mantle lithosphere through extension and relatively small variations in the present-day thermal lithosphere thickness. The new temperature model can be used to constrain geodynamic processes and lithosphere structure and rheology, and it can serve as a first-order boundary condition for geothermal exploration.